BUSINESS MODEL ANALYSIS IN KARTINIPEDIA APPLICATION USING BUSINESS MODEL CANVAS (BMC) APPROACH - Erika Ayu Amelia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Technological developments have had a major impact on the world of trading, especially the progress of the market which has shifted from the offline market to the digital/online market. Online media developed in the form of applications that can be downloaded via smartphones or also called e-commerce. One of those who took part in this opportunity was the Kartinipedia Application: Center for Women's Needs. Kartinipedia is a special application for women to get products and psychological needs. The research method used is descriptive qualitative analysis. Collecting data using observation and interview techniques. Based on calculations using the System Usability Scale (SUS), Kartinipedia obtained a score of 67.83, which means that the system and business model need to be improved. The purpose of this research is to identify the business model that has been implemented by the Kartinipedia application using the Business Model Canvas approach and to formulate an alternative development strategy by improving the new business model. The resulting finding is the need to change the Kartinipedia application's business model. Among them is to clarify customer segments by dividing them into five segments, namely sales, buyers, consultants and clients. The five segments have five different value propositions so that later all BMC elements will be in more detail to create new strategies in developing the company.